Scientific and Quantitative Literacy and Its Influence on Academic Achievement in Physical Science - Estillena, Rea Joy; Linaugo, Joji (Technium Social Sciences Journal, 2025)
Many students found Physical Science to be a particularly challenging subject despite its recognized importance. Thus, this study aimed to assess the levels of scientific literacy (SL), quantitative literacy skills (QLS), and academic achievement in Physical Science (AAP) among Grade 12 students. The study also investigated the relationships among these variables. The respondents were 231 Grade 12 students selected through stratified random sampling. The study is utilizing a researcher-made questionnaire to gather data on the academic achievement in Physical Science, and adapted questionnaires to measure scientific and quantitative literacy. The collected data were analyzed using mean, standard deviation, and spearman rank-order. Meanwhile, the researcher abided to the Philippine Health Research Ethics Board (PHREB). Results indicated developing interpretation of scientific literacy and quantitative literacy skills among the students, whereas results in terms of Physical Science academic achievement were interpreted at the approaching proficiency level. Significant positive correlations were found between both scientific and quantitative literacy and academic achievement in Physical Science. Thus, the study validated Jean Piaget’s Constructivist Learning Theory and John Dewey’s Progressive Education. With these, future studies may conduct more in-depth analyses using a mixed-method design to further explore the factors influencing students’ academic achievement in Physical Science.